INTRODUCTION: MEDIA, RELIGION AND RELIGIOSITY IN THE DIGITAL AGE - De Sousa, Marco Túlio; Tudor, Mihaela-Alexandra; Evolvi, Giulia (TROPOS: COMUNICAÇÃO, SOCIEDADE E CULTURA (ISSN: 2358-212X), 2021)
The presence of religion on the Internet is growing globally. This special issue aims at analyzing how religious groups and individuals employ digital media, how religion is represented online, and how new technologies shape the practice of contemporary religion. With articles in different languages focusing on various contexts, this special issue explores religious authorities, practices, communities, conflicts, and spiritualities in the digital age, with a theoretical attention to the field of religion and digital media.